2021
DOI: 10.1016/j.clinimag.2020.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Beyond business as usual: Radiology residency educational response to the COVID-2019 pandemic

Abstract: The COVID-19 pandemic has disrupted standard hospital operations and diagnostic radiology resident education at academic medical centers across the country. Deferment of elective surgeries and procedures coupled with a shift of resources toward increased inpatient clinical needs for the care of COVID-19 patients has resulted in substantially decreased imaging examinations at many institutions. Additionally, both infection control and risk mitigation measures have resulted in minimal on-site staffing of both tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…With these lessons in mind, there is a potential role for a more centralised/national resource for teaching radiology registrars to minimise discrepancies in trainee education. 19 Local teaching could focus on the much desired return to face-to-face "hot-seat" teaching. It seems likely that a combination of face-to-face and remote teaching will continue in future and the fact that teaching quality was maintained through the first wave of the pandemic suggests that remote teaching can be delivered effectively.…”
Section: Impact On Uk Teachingmentioning
confidence: 99%
“…With these lessons in mind, there is a potential role for a more centralised/national resource for teaching radiology registrars to minimise discrepancies in trainee education. 19 Local teaching could focus on the much desired return to face-to-face "hot-seat" teaching. It seems likely that a combination of face-to-face and remote teaching will continue in future and the fact that teaching quality was maintained through the first wave of the pandemic suggests that remote teaching can be delivered effectively.…”
Section: Impact On Uk Teachingmentioning
confidence: 99%
“…In many institutions, teaching rounds were canceled initially, but were shortly resumed in a virtual setting, taking advantage of platforms such as Zoom, Google Hangouts/Meet, Microsoft Teams, or Skype. 4 , 5 Recorded grand rounds from previous years, 1 participation in internal medicine rounds in preparation for redeployment, 6 and weekly or daily didactic radiology teaching rounds continued virtually. 4 , 7 , 8 One study that surveyed radiology residents showed the majority of residents were satisfied with the virtual delivery of teaching rounds.…”
Section: Teaching Roundsmentioning
confidence: 99%
“… 2 , 5 A number of virtual learning strategies were also employed including, gamification, 16 digital polling, 5 , 9 , 20 and case-based learning. 6 , 7 , 21 , 22 For the most part, residents prefer the in-person experience for teaching and learning. 23 A minority seem to prefer virtual learning.…”
Section: Virtual Learning and Flipped Classroom Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Didactic lectures and multidisciplinary conferences also have transitioned to a virtual platform. Software-based conference room solutions have allowed for these activities to continue in a virtual setting (1)(2)(3)(4)(5)7).…”
Section: Introductionmentioning
confidence: 99%